Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Tai (Team Assisted Individualization) Terhadap Aktivitas Belajar Siswa - Sinta Aprilianti; Rita Zahara; Ria Herdhiana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Langlangbuana, 2012)
The method used in the research is the method of the experimental method. The nature of the research used in this study is quantitative research. The sample in this study was students of class XI IPS 3 into the experimental class and XI IPS 4 became the control class. This experimental study measures attitudes, so using data collection techniques done with non-tests, namely through observation or observation, obtained the interpretation of the observations of student learning activities in the experimental class is 75% with a good category compared to the control class. These results directly prove that in the experimental class with the application of the TAI Cooperative Learning Model there is an increase compared to the experimental class. In accordance with the. the results of the processing of the difference test are obtained t count table 11.208> t table (40; 0.05) is 1.684, then H1 is accepted and H0 is rejected.